Public expenditure on hospitalizations for COVID-19 treatment in 2020, in Brazil - Hebert Luan Pereira Campos dos Santos; Fernanda Beatriz Melo Maciel; Geovani Moreno Santos Junior; Poliana Cardoso Martins; Nília Maria de Brito Lima Prado
ABSTRACT OBJECTIVE Describe the expenditure resulting from hospitalizations for clinical treatment of users diagnosed with COVID-19 in the Unified Health System (SUS) between February and December 2020. METHODS This is a descriptive study based on data from the Hospital Information System about government expenditure on hospitalizations for clinical treatment of users diagnosed with COVID-19 and causes included in the ICD-10 chapters. We obtained the number of hospitalizations, average length of stay, lethality rate, and total expenditure considering hospital services, professional services and average expenditure per hospitalization. RESULTS In the period evaluated, SUS registered 462,149 hospitalizations, 4.9% of them for COVID-19 treatment. Total expenditure exceeded R$ 2.2 billion, with 85% allocated to hospital services and 15% to professional services. Expenditure for treating COVID-19 was distributed differently between the country's regions. The Southeast region had the highest number of hospitalizations, highest total amount spent, highest average length of stay in days, and highest lethality rate; the South region, in turn, recorded the highest percentage of spending on non-profit hospitals (58%) and corporate hospitals (15%). CONCLUSIONS Hospitalizations for clinical treatment of coronavirus infection were more costly compared to those for treatment of acute respiratory failure and pneumonia or influenza. Our results show the disparities in hospitalization expenditure for similar procedures between the regions of Brazil, underlining the vulnerability and the need for strategies to reduce the differences in access, use, and distribution of SUS resources, ensuring equanimity, and considering the unfair inequalities between the country's regions.